Penggunaan Sabun Pembersih Vagina Dengan Kejadian Keputihan Pada Wanita Usia Subur: Use of Vaginal Cleansing Soap with Vaginal Discharge in Women of Childbearing Age - Sinapa, Lelyans Surya Risma (Chakra Brahmanda Lentera Institute, 2022)
Reproductive health among women must get serious attention, one of which is leucorrhoea, which is a problem associated with a female sexual organ. Leucorrhoea is usually caused by a fungus or bacterial virus which of course this problem is very disturbing to the sufferer. Objective To find out the relationship between the use of vaginal cleansing soap and vaginal discharge in fertile age women in Kasiguncu sub-district, Poso Pesisir district, Poso regency. The design used in the study was observational study population was all fertile age women with vaginal discharge. The sample size is 120 respondents using the Independent Variable Purposive sampling technique of research is vaginal cleansing soap. The dependent variable is Leucorrhoea Data was collected using a questionnaire, then the data were analyzed using Chi Square test with a significance level of α ≤ 0.05. The results showed that most respondents had 77 vaginal cleansers (64.2%), and 79 respondents (65.8%) used vaginal cleansing soap. The statistical test in this study used a chi-square test with a <0.05 obtained p = 0,000 where H1 was accepted and H0 was rejected which means that there is a relationship Use of Vaginal Cleansing Soap with Leucorrhoea in Fertile Age Women in Kasiguncu Village, Poso Pesisir District Poso. There is a relationship between the Use of Vaginal Cleansing Soap and Leucorrhoea in Fertile Women in Kasiguncu Village, Poso Pesisir District, Poso Regency. Using the right soap can prevent vaginal discharge.